PENGARUH PEMBERIAN BEASISWA BIDIK MISI TERHADAP MOTIVASI BERPRESTASI DAN DISIPLIN MAHASISWA PENERIMA BEASISWA BIDIK MISI DI KOTA PALEMBANG - Dian Septianti (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this study was to determine and analyze the effect of Bidik Misi scholarship toward achievement motivation and discipline of Bidik Misi scholarship in Palembang. Types of data used were primary data and secondary data, collection techniques were questionnaires, interviews and documentation. The sampling technique used accidental sampling by the number of respondents was 100 respondents. The analysis model used two stage leasts ordinary square. The study concluded that Bidik Misi Scholarship programs had significant effect on achievement motivation Bidik Misi scholarship students in Palembang with a significance of 0.000, but did  not affect the discipline of scholarship students Bidik Misi in Palembang with a significance of 0.732.Keywords: Scholarship, Achievement Motivation, Discipline